2002
DOI: 10.1021/jf0258003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Backhousia citriodora:  Antibacterial and Antifungal Activity

Abstract: Backhousia citriodora products are used as bushfoods and flavorings and by the aromatherapy industry. The antimicrobial activity of 4 samples of B. citriodora oil, leaf paste, commercial tea (0.2 and 0.02 g/mL), and hydrosol (aqueous distillate) were tested against 13 bacteria and 8 fungi. Little or no activity was found to be associated with the leaf tea and hydrosol, respectively. Leaf paste displayed antimicrobial activity against 7 bacteria including Clostridium perfringens, Pseudomonas aeruginosa, and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 16 publications
8
82
1
1
Order By: Relevance
“…This lower sensitivity of Gram negative organisms has been related to the presence of an outer membrane surrounding their cell wall, which restricts the diffusion of hydrophobic compounds through its lipopolyssacharide covering (34). It has been reported that among Gram negative bacteria, P. aeruginosa appears to be least sensitive to essential oils (18,21,38). Therefore, this behavior was not observed in our study, because P. aeruginosa showed an MIC value similar to other Gram negative assayed bacteria, as well as did not develop smallest inhibition zones.…”
Section: Discussionmentioning
confidence: 57%
“…This lower sensitivity of Gram negative organisms has been related to the presence of an outer membrane surrounding their cell wall, which restricts the diffusion of hydrophobic compounds through its lipopolyssacharide covering (34). It has been reported that among Gram negative bacteria, P. aeruginosa appears to be least sensitive to essential oils (18,21,38). Therefore, this behavior was not observed in our study, because P. aeruginosa showed an MIC value similar to other Gram negative assayed bacteria, as well as did not develop smallest inhibition zones.…”
Section: Discussionmentioning
confidence: 57%
“…Some studies expressed that plant extracts and EO components appear to make the cell membrane permeable and are able to disintegrate the outer membrane of Gram-negative bacteria and these are slightly more active against Gram-positive than Gram-negative bacteria (Burt 2004;Abdollahzadeh et al 2014). However, not all researches on EOs have concluded that Gram-positive bacteria are more susceptible (Wilkinson et al 2003). The antimicrobial activity of essential oils and plant extracts would be related to the respective composition and structural configuration of the plant volatile oils, their functional groups and possible synergistic actions and reactions between components (Mahmoodi et al 2012).…”
Section: Plant Natural Antimicrobial Compounds: Composition and Actiomentioning
confidence: 99%
“…The strain with the lowest susceptibility was P. aeruginosa (MIC=MBC=50 μl/ml). This strain is very resistant to most of the essential oils, owing to the hydrophilicity of its cell membrane surface [18][19][20][21]. Except for the strains K. pneumoniae and S. aureus, the oil had both inhibitory and bactericidal effect at the same concentration (MIC=MBC).…”
Section: Antimicrobial Activity Of S Hortensis Essential Oilmentioning
confidence: 99%